Les paroissiens de Saint-Pierre du Queyroix de Limoges et la communauté des prêtres - Anne Massoni (Medievalista)
The church of Saint-Pierre du Queyroix in Limoges has been home to the city's largest and most respectable parish since at least the Middle Ages. Situated a stone's throw from the Abbey of Saint-Martial, in the district known as le Château – as distinct from la Cité – it was the centre of the religious and sacramental life of the surrounding families, including a wealthy and influential bourgeoisie. It was therefore natural for these families to turn to the clergy of this parish to take care of their memory after their demise. The parish was also home to a community of priests, a sort of proto chapter, which was already very well structured in the fourteenth and fifteenth centuries and who received donations for the salvation of souls from members of these families. The collections held by the Archives départementales de la Haute-Vienne (G series) allow an analysis of the relationships forged between laymen and clerics at this time and a special focus on several parishioners.